Change rates of soil inorganic carbon vary with depth and duration after land conversion across drylands in North China. (June 2023) - Wang, Zhufeng; Wang, Yugang; Feng, Wenting
Abstract: Soil inorganic carbon (SIC) accounts for 30–70% of the total soil C in global drylands. Despite the slow turnover rate, recent studies indicate that SIC could be altered by land-use change as soil organic C (SOC). Neglecting SIC change could contribute greatly to the uncertainty of soil C dynamics in drylands. However, due to the spatial-temporal variation in SIC, the direction and magnitude of SIC change (rate) induced by land-use change at a large spatial scale is understudied and poorly understood. Here, we used the space-for-time approach to test how the SIC change varied with the duration and type of land-use change and soil depth across China's drylands. We assessed the temporal and spatial variations in the SIC change rate and explored the influencing factors based on a regional dataset comprising 424 pairs of data across North China. We found that the SIC change rate of 0–200 cm after land-use change was 12.80 (5.47‒20.03) g C m −2 yr −1 (mean with 95% confidence interval), which was comparable to the SOC change rate (14.72, (5.27-24.15 g C m −2 yr −1 )). Increased SIC occurred only in deep soils (>30 cm) and in the conversion from deserts to croplands or woodlands. In addition, the SIC change rate decreased with the duration of land-use change, implying that quantifying the temporal pattern of SIC change is necessary to accurately estimate SIC dynamics. The SIC change was strongly related to changes in soil water content. The SIC change rate was weakly and negatively correlated with the SOC change rate, and this relationship varied with soil depth. Together, this study highlights that to improve the prediction of soil C dynamics following land-use change in drylands, we should quantify the temporal and vertical patterns of both soil inorganic and organic C changes in the region. Graphical abstract: Image 1 Highlights: Inorganic C of deep soils increased after land-use change across China's drylands. The SIC change rate displayed a decreasing trend with duration of land-use change. The SIC change rates after land-use change were comparable to the SOC change rates. SIC changes were negatively and weakly correlated with SOC changes.